How Creativity is Changing China - Wuwei, Li (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The question Professor Li Wuwei investigates is not 'whether' creativity is changing China - but 'how' creativity is changing China. The outcome will have a profound impact on how China develops and its economic role in the world. Creative industries maintain and protect historical and cultural heritage, improve cultural capital, and foster communities as well as individual creativity. This leads to the improvement of cultural assets of cities, the establishment of city brands and identity, the promotion of the creative economy, and overall economic and social development. In this context, creativity is changing China forever.